PENTINGNYA PENDIDIKAN KARAKTER UNTUK SISWA SEKOLAH DASAR DI ERA DIGITAL DI DUKUH KUNCEN KECAMATAN CAWAS - Agus Nur Ikhsan; Adnan Maulana Ihsanudin; Putri Zudhah Ferryka; Heldan Edwin Muhammad Nur (Bajang Institute, 2023)
Character education really needs to be instilled in elementary school children in this digital era. This character education is an attempt to implement religious values, morality, student ethics through knowledge, also with the help of parents, teachers, a community that is very important for the formation and development of the character of the participants. Every child has good potential from birth, but this potential must be preserved, adjusted and socialized properly so that the character of each child is formed and developed. In the digital era, children can also use digital media without digital constraints. The digital era not only has positive effects, but also negative behavior effects are also the responsibility of teachers, parents, and the adult community to monitor and control what children do with their digital media, so that children can make the best use of their digital media. -good